Analisis Pemasaran Sayuran di Pasar Inpres Ruteng Kabupaten Manggarai - Ronaldus Don Piran; Polikarpus Payong; Astried Priscilla Cordanis (Forum Agribisnis, 2022)
Vegetable production is still relatively low in Manggarai Regency. This is a challenge because they have to bring in vegetable products from outside the region. This study identifies vegetable marketing channels and assesses the efficiency of vegetable marketing channels by focusing on tomatoes, beans, mustard greens, and kale, as are often found in the Inpres Market in Ruteng City. The analytical techniques used are marketing margin analysis, farmer acceptance percentage analysis (F's) and marketing efficiency analysis (Ep). Vegetable marketing channels at the Ruteng Inpres Market consist of Farmers - Consumers, Farmers - Retailers - Consumers, Farmers - Middlemen - Retailers - Consumers. Based on the difference (difference) in prices at farmers and prices at consumers, marketing of tomatoes using channel II is more efficient, while marketing of mustard, beans and kale using channel III is more efficient. Marketing of tomatoes, beans and kale using channel II is more efficient when viewed from the large percentage of farmers' income compared to marketing mustard greens. Based on the profit margin percentage, marketing channel II is more profitable for retailers than channel III, because middlemen take a larger percentage of profits than retailers in marketing channel III. Based on the comparison of marketing costs with selling prices, marketing of tomatoes, mustard greens and beans in channel III is more efficient than channel II, except for marketing of kale. Tomato, chickpea and kale farmers are advised to apply marketing channel II. The middleman in marketing channel III needs to reduce the percentage of profit taking so that the retailer is able to get a profit that approximates the profit of the middleman. Farmers and other marketing institutions need to use standard weight measuring devices in marketing their products at the Ruteng Inpres Market.